Användardriven kompetensutveckling : En studie av ett nätverksbaserat verktygs användningsområde - Hedlund, Fredrik (2012)
Luleå municipality is an organization that has been working a long time with making improvements to their competence development. Luleå municipality is an organization with over 7000 employees that are employed in different fields and it is therefore of great value to the municipality that their employees have high competence. Luleå municipality continuously works to develop their competence development and it has led to them testing new models. One of the models the municipality has decided to test revolves around a networking tool. The testing of the tool was performed by groups of human resources employees from different organizations through participation in a project called CLN (Collaborative Learning Networks).The purpose of the study is to see if Luleå municipality has had any use of the networking tool and the project and to create a deeper understanding of the uses the tool can have in the work with competence development. In the study it is made apparent that deficits in the networking tool create problems that hinder the competence development, but also that competence development can be attained trough the tool. It is also attained that that the participants in the study have learned the value of a networking tool during the project. Validerat; 20121123 (global_studentproject_submitter)